Tracking e-reading behavior: uncovering the effects of task context, electronic experience, and motivation - Vuorinen, Pauliina Tea Eleonoora; Tatler, Benjamin W.; Keller, Frank (Frontiers in Education, 2024)
Although electronic reading of fiction has become mainstream, little is known about how electronic texts are read, and whether this behaviour is connected to readers' motivation or experience reading electronically. To address this gap, sixty undergraduate students' reading behaviour was tracked while reading a 15-page short story. A novel method was used to study participants' frequency of task-switching, their reading speed, and navigational patterns unobtrusively, outside of the lab. Reading behaviour was analysed by two multilevel models to assess (1) whether variance in behaviour could be predicted by the task context, such as location in text or timing of reading sessions, and (2) whether behaviour was connected to participants' situational motivation to read the short story, their contextual motivation towards reading as an activity, or their task-relevant electronic experience. Our results showed that highly experienced and avid readers reacted to text difficulty more adaptively, indicating that motivation and electronic experience may have a key role in supporting comprehension. In contrast, situational motivation was not associated with reading behaviour, contrary to our expectations. These findings provide a significant contribution to our understanding of e-reading, which can be used as a foundation to support recreational reading engagement on digital devices.